The Development and Pre-Clinical Anti-Inflammatory Efficacy of a New Transdermal Ureasil-Polyether Hybrid Matrix Loaded with Flavonoid-Rich Annona muricata Leaf Extract - Camila Beatriz Barros Araújo; José de Oliveira Alves Júnior; Mariana Rillo Sato; Kammila Martins Nicolau Costa; Jéssica Roberta Lima; Bolívar Ponciano Goulart de Lima Damasceno; Francisco José Batista de Lima Junior; Bruna Galdorfini Chiari Andréo; Vanda Lucia dos Santos; João Augusto Oshiro-Junior (MDPI AG, 2024)
This study aimed to develop a novel ureasil-polyether transdermal hybrid matrix (U-PEO) loaded with Annona muricata concentrated extract (AMCE), which exhibits potent anti-inflammatory activity. The extract was obtained by maceration, a method that allowed for the extraction of a high concentration of flavonoids (39.27 mg/g of extract). In vivo tests demonstrated that 10 mg/kg of AMCE inhibited inflammation for 6 h. The physicochemical characterization of U-PEO with AMCE was conducted via a thermogravimetric analysis (TGA), while its surface was recorded using atomic force microscopy (AFM). The in vitro macroscopic swelling and release tests demonstrated the hydrophilic profile of the material and the percentage of AMCE released. The TGA results demonstrated that the system exhibited physical compatibility due to the thermal stability of U-PEO. Additionally, the AFM analysis revealed a rough and porous surface, with a particular emphasis on the system with AMCE. The release resulted in the liberation of 23.72% of AMCE within 24 h. Finally, the preclinical tests demonstrated that U-PEO with AMCE was also capable of effectively inhibiting inflammation for 6 h, a duration comparable to that of a commercial formulation. The results permit the advancement of the study towards the development of a transdermal system, thereby rendering its application in clinical studies feasible.